Central Asia : The New Silk Road Initiative’s Questionable Economic Rationality - Peyrouse, Sebastien; Raballand, Gael (Taylor and Francis, 2016)
This paper explores how the New Silk Road Initiative, which is presented as a concept founded on economic rationality, tends to offer an ideological perspective on transport and trade for the Central Asian region. The New Silk Road Initiative advocates for more transport infrastructure in Central Asia without tackling the most significant barriers to trade: production patterns, widespread corruption, and poor management practices at borders.